Anti-inflammatory and Insulin-sensitizing Effects of Combined Pandanus amaryllifolius and Syzygium polyanthum Extracts in HFD-STZ Induced Diabetic Rats - Meilinda, Selvia; Lim, Hadyanto; Anto, Endy Juli; Siahaan, Jekson M; Tarigan, Menang B (Universitas Sam Ratulangi, 2026)
Type 2 Diabetes Mellitus (T2DM) is a global health crisis characterized by insulin resistance and pancreatic -cell failure, largely driven by chronic low-grade inflammation. Elevated pro-inflammatory markers, particularly TNF- and IL-6, disrupt insulin signaling. While conventional oral hypoglycemics are effective, their long-term use is often hindered by adverse effects. Pandanus amaryllifolius and Syzygium polyanthum are polyphenol-rich medicinal plants with significant antioxidant potential. This study evaluates the in vivo efficacy of a combined ethanolic extract of these plants in reducing TNF-, IL-6, and HOMA-IR levels, alongside in silico validation of their bioactive compounds. An experimental posttest-only control group design was employed using HFD-STZ-induced male Wistar rats. Key parameters included blood glucose, HOMA-IR, inflammatory cytokines, and pancreatic histopathology. Molecular docking was conducted to analyze the interaction between bioactive compounds and glucose metabolism receptors. The combined extracts significantly suppressed systemic inflammation, marked by a substantial reduction in TNF- and IL-6. This correlated with improved insulin sensitivity and lower HOMA-IR values. Histopathologically, the 200 mg/kg BW dose showed the most significant recovery of the islets of Langerhans. In silico analysis confirmed that flavonoids like quercetin exhibit strong binding affinities to target proteins. The combination of P. amaryllifolius and S. polyanthum acts as a potent anti-inflammatory and insulin sensitizer, offering a promising adjuvant therapy for T2DM management.